Know your Bible ; v. 1 a brief introduction to the Bible - Scroggie, William Graham, 1877-1958 (London, UK Pickering and Inglis)
Contents : v. 1 : Analytical ; the Old Testament. Includes index.
First published in 1940 (Dictionary of Scottish church history and theology).
Keywords: Bible. O.T. -- introductions